Single Nucleotide Polymorphism rs1800497 in Risperidone and Aripiprazole Therapy for Schizophrenia Patients - Benedictus Wicaksono Widodo; Mgs. M. Irsan Saleh; Theodorus Theodorus (Universitas Lambung Mangkurat, 2021)
Schizophrenia is a variable of psychopathologic syndrome involving cognition, emotion, perception, and other behavioral aspects. Therapies on schizophrenia is solely based on history of mental illnesses and mental status. Schizophrenia affecting 1.1 million persons globally in 2017; 70.8% of them happened in 25-55 years old. This study was conducted in mental hospital in Palembang, Indonesia. Blood samples was taken from clinically diagnosed schizophrenia patients (20 patients taking aripiprazole and 60 patients taking risperidone) under therapy. DNA was extracted using Chelex 100 method and digested using Taq1 enzyme. DNA was electrophoresized and visualized. CC allele was found in 10% of patients taking aripiprazole and 11.67% patients taking risperidone. CT allele was found in 70% patients taking aripiprazole and 76.67% patients taking risperidone. TT allele was found in 20% patients taking aripiprazole and 11.67% patients taking risperidone. ANKK1 Taq1A polymorphism in schizophrenia patients shows different therapeutic response with worse therapeutic response compared to patients with normal allele.